The Transformation of Rudrah Dance from Bedhaya to Srimpi: An Analysis Based on Written Sources - Windri Estri Puspitaningrum; Slamet MD (Riviera Publishing, 2025)
This research aims to reveal the reasons behind the transformation of Rudrah dance from bedhaya to srimpi by Wahyu Santoso Prabowo. This transformation is rooted in the basic idea of Rudrah bedhaya dance, although the documentation is limited to written notes and photographs. This research is based on the analysis of the 1979 Rudrah dance manuscript to explore the creative process, chronology, and reasons behind the transformation. The method used is qualitative with a historical approach and text analysis. Data were obtained through document studies, archives, in-depth interviews, and academic literature covering movements, floor patterns, accompaniment, and socio-cultural context. The interview with Wahyu Santoso Prabowo aimed to gain a deeper perspective on the interpretation of Bedhaya and Srimpi elements in the context of form transformation. The results showed that the fundamental changes started from the manuscript traces to become a new dance form. These changes are fully realized by the choreographer to improve the aesthetic side and contextualization with the times. The visual changes that occur in Rudrah dance include changes in the form of dance performances related to changes in choreographic structure, clothing, getting accompaniment, and duration which aim to improve aesthetics and relevance in the modern era without losing its philosophical essence. This transformation becomes an innovative strategy for preserving traditional dance